Development of high-strength lightweight concrete with expanded clay aggregate - Peerawat Parnporamat; Punchet Thammarak; Raktipong Sahamitmongkol; Pennung Warnitchai; Thanakorn Pheeraphan; Royal Thai Government (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
In many constructions nowadays, concrete is chosen as construction material because of its strength and price. Concrete is the product coming from the combination of many materials which are cement, water, coarse aggregates, and fine aggregate. Moreover, concrete is chosen as the most use of material in high-rise buildings. According to 2Council on Tall Building and Urban Habitat 3, the building height tends to be higher. However, conventional concrete that is mostly used to construct high-rise building has approximate density about 2400 kg/m3 , and its weight is the most of load acting in the high-rise building which restricts the height of building in some cases. Therefore, in high-rise buildings engineers try to reduce the self-load of structure as much as possible in order to reduce the structural members{u2019} dimension such as column, beam, and foundation to reduce the cost of construction or construct higher floor within the same structural system members. Consequently, lightweight concrete was made to satisfy this purpose. One of the ways to make lightweight concrete is use lightweight aggregate as aggregate in concrete to replace the normal weight. Normally, the strength of lightweight aggregates that is used to make lightweight concrete is lower than normal weight aggregates. According to Ahmad, Chen, & Shah (2019), the weakest component of the concrete determines strength of concrete. Therefore, using lightweight aggregate as aggregate in concrete may reduce the concrete{u2019}s strength because of lightweight aggregate{u2019}s strength. However, in high-rise building the concrete{u2019}s strength should be equal to conventional concrete or be high-strength concrete to bear with the load occurring in high-rise building. In order to make the lightweight concrete with the equal or higher of compressive strength than conventional concrete, the lightweight aggregate with enough strength and higher strength of cement paste should be used to combine together to produce the concrete. Consequently, expanded clay aggregate (ECA) is applied to make the high-strength lightweight concrete because of the unique characteristics of ECA which is light and its strength.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Lightweight concrete; Aggregates (Building materials)